Validity and reliability of the Persian version of the exercise self-efficacy scale in people with multiple sclerosis - Faride Goldoust; Maryam Abolhasani; Elham Shakibazadeh; Mehdi Yaseri; Gholamreza Garmaroudi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Exercise self-efficacy has been identified as one of the primary determinants of physical activity in people with multiple sclerosis (MS). Therefore, assessment of exercise self-efficacy is important to be measured with valid and reliable scale to provide tailored interventions. MATERIALS AND METHODS: The English version of the exercise self-efficacy scale was translated into Persian using a forward-backward translation approach. Factorial validity was conducted using the expletory factor analysis (EFA) and the confirmatory factor analysis (CFA). In addition, construct validity was performed using convergent and known-group validity. Reliability was evaluated by internal consistency and test-retest reliability. Participants were recruited from two hospitals (MS clinics). RESULTS: Expletory factor analysis identified a single factor structure which explained 64.7% variance in exercise self-efficacy scale (EXSE). CFA supported a single factor structure with a good model fit. Average variance extracted = 0.60 and composite reliability = 0.93 values confirmed the convergent validity. The known-group validity was verified with significant differences between subgroups. The Cronbach's alpha coefficient = 0.93 and intraclass correlation coefficient = 0.85 supported reliability of EXSE scale. CONCLUSIONS: Our findings provided sufficient evidence of validity and reliability for EXSE scale in people with MS. This measure can utilize by researchers and health-care providers in studies and clinical practice as a robust measure to assess exercise self-efficacy and to develop interventions in people with MS.